Quality of life of children with acute lymphoblastic leukemia - Arifah, Siti; Pookboonmee, Renu; Patoomwan, Autchareeya; Kittidumrongsuk, Prasong; Andarsini, Mia Ratwita (Indonesian Pediatric Society, 2023)
Background Acute lymphoblastic leukemia (ALL) is the most common cancer in children worldwide, which requires long treatment. This condition and its subsequent treatment change the body's physiology, reducing children’s quality of life. Objective To describe the quality of life in children with acute lymphoblastic leukemia in Java, Indonesia. Methods This descriptive study with a cross-sectional approach included parents who had children with ALL at three referral hospitals in Java, Indonesia, between January 2021 and May 2022. We recruited 188 mothers or fathers who accompanied their children for follow-up visits or hospitalization. Children’s quality of life as the primary outcome was evaluated by parent proxy using the PedsQL 3.0 cancer module. Results Most parents were mothers (81.9%); parents’ ages ranged from 22 to 59 years. The mean age of children was 7.63 (SD 3.85) years, with 63.3% boys and 147 (78.2%) treated in maintenance phase during the study. The mean overall children’s QoL score was 84.37 and it classified as high (73.9% of subjects), no children had very low QoL. The lowest mean sub-scale QoL score was in procedural anxiety (72.25), whereas the highest sub-scale score was in communication (91.56). Conclusion There is an improvement in QoL of children with ALL in Indonesia. However, the procedural anxiety sub-scale requires more interventions to reduce anxiety and alleviate pain during invasive procedures.